Role of counseling in the prevention of childhood obesity - Alradha, Abdulaziz Habib; Aljumaie, Maha Aid; Alanzi, Reem Basher; Alqurashi, Bushra Haider; Aldhawi, Faris Saleh; Alqayawi, Nura Saleh; Alahmadi, Mariah Omar; Farran, Raneem Ibrahim; Alayyafi, Wed Ahmed; Niyazi, Razan Abdulshakur; Alsadq, Sumih Abdullah (International Journal Of Community Medicine And Public Health, 2021)
Children tend to gain weight and develop obesity by the age of 9 months old. Therefore, it is essential to apply early interventions as early as this period because childhood obesity does not usually spontaneously resolve by age. Medical counseling with obese children and their caregivers is an essential interventional approach that can enhance the quality of care and the related outcomes. In this literature review, we have discussed the role of professional counseling in the management of pediatric obesity. Healthcare professionals can help caregivers to establish proper dietary intake with specific amounts of calories based on the administered food items per day to maintain healthy dietary habits. Taking care of any associated morbidities should also be considered. For instance, adequate care should be provided for obese children with DM to help them maintain optimal blood glucose levels by using healthy diets, exercising, and taking blood glucose-lowering medications. However, precautions should be considered as these patients might be subjected to hypoglycemic attacks as a result, which might increase their morbidity and mortality. Children and caregivers' education is a critical approach to enhance compliance and increase awareness of the management and interventions. Finally, further efforts should also be directed to the healthcare givers to make them more aware of the benefits of sticking to the guidelines and the importance of counseling in prevention and management.